Ayurvedic Management of Mukhapaka; Chronic Recurrent Aphthous Stomatitis in children (International Journal of Food and Nutritional Sciences, 2021)
Recurrent aphthous stomatitis or ulcerative stomatitis is a common disorder of the oral cavity and pharynx. It is a condition that causes pain, swelling and sores inside the oral cavity. These are white ulcers with surroundings erythema, located on the oral mucosa, tongue and pharynx. It can be caused by a disease, an infection or because of irritating foods and chemicals. This kind of stomatitis can be corelated to Mukhapaka. Mukha paka is one of pittaja vikara where paka and vruna are formed inside the mukha associated with toda raga and daha. This article will highlight the Ayurvedic approach and management of Mukhapaka in children with a case report of a 12-year-old male child presented with a 2-year history of episodes of multiple recurrent ulcers all over the mouth.